Anatomical characteristics of the pubic symphysis of the second period of adulthood according to computer tomography data - I. A. Balandina; A. V. Klimets; A. A. Balandin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
There is a truly unique anatomical structure in the human body that connects the two articular surfaces of the pubic bones of the pelvis. This is the pubic symphysis. When analyzing the modern scientific literature, it becomes obvious that there is a whole large trend devoted to determining the "morphofunctional norm" for a specific age period of human life using lifetime imaging techniques. The aim of the study was to determine the height, width, thickness, and X-ray density of the pubic symphysis in men and women in the second period of adulthood using computed tomography (CT) imaging techniques.Object and methods. The work is based on the results of CT examination of 31 men from 36 to 60 years old and 25 women from 36 to 55 years old with normal pelvic dimensions without pathology of its bones and ligaments, as well as pelvic organs Each of them obtained consent for the study, which was performed as indicated to exclude possible pathology of pelvic bones. The CT study consisted of determining the width, height, and thickness of the pubic symphysis, as well as determining the X-ray density in its upper and lower sections. Results. Comparative analysis of the data reveals a tendency to predominance of the parameters of width, thickness and X-ray density in the upper part of the pubic symphysis in the sample of male subjects (p > 0.05). The parameters of X-ray density in the lower parts of pubic symphysis have insignificant prevalence in the sample of female subjects (p > 0,05). At the same time, the indices of pubic symphysis height are practically equal in both sexes.Conclusion. The obtained results of lifetime analysis of height, width, thickness of pubic symphysis and X-ray density in its upper and lower parts in individuals of both sexes in the second period of adulthood expand scientific ideas about its structure, allowing to reproduce specific characteristics of its age-sex norms.